Pengaruh Penggunaan Aplikasi Tiktok Dan Brand Awareness Terhadap Minat Beli Produk Kecantikan Implora Di Malang - Risma Khoyrunnisa; Nur Hidayati; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of the use of Tiktok Applications and Brand Awareness on Interest in Buying Implora Beauty Products in Malang. The type of research used is explanatory research with the method of distributing questionnaires. The sample in this study were 72 people and data processing using the SPSS program. This study has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The variables used in this study are the dependent variable, buying interest, and the independent variable, namely the use of the Tiktok application and brand awareness. The results of the study concluded that the variables of the use of Tiktok Applications and Brand Awareness had a positive effect on the Buying Interest of Implora Beauty Products in Malang. Keywords: Purchase intention, Tiktok Application Usage and Brand Awareness